NON PHACO SUTURE LESS CATARACT EXTRACTION THROUGH TEMPORAL APPROACH - Junejo, Sameen Afzal; Jatoi, Shafi Muhammad; Khan, Nisar Ahmed (Journal of Ayub Medical College Abbottabad, 2009)
Background: Non Phaco suture less cataract extraction through temporal approach retains most of the advantages of phacoemulsification but can be delivered at lower cost with better visual out come. Methods: Extra capsular cataract extraction followed by posterior chamber intraocular lens implantation was performed, on 300 eyes of 250 patients. The technique involved was posterior limbal corneal tunnel incision through temporal approach, followed by implantation of PMMA posterior chamber intraocular lens. Visual acuity at the time of discharge, third post operative week and sixth week was recorded. Surgically induced astigmatism was reported. Results: The uncorrected visual acuity at discharge was 6/18 or better in 63.2% eyes. The best corrected visual acuity was 6/9 and better in 96.0% subjects at six weeks. Poor visual outcome (<6/60) occurred in 0.5% eyes. 0.4% subjects had posterior capsule rent followed by vitreous show. There was no increase in against the rule astigmatism, as the corneal incision was given through temporal approach. Conclusion: Suture less manual extra capsular cataract surgery through temporal approach ensures rapid visual recovery with minimum astigmatism against rule. Keywords: Astigmatism, Cataract, extraction, corneal tunnel incision, temporal approach, Phaco